Bahari Technopark Tegal - Ma'rufinanto, Sandy, Dr. Ir. Arya Ronald, Ir. Nurhasan, MT (2016)
Tegal City is a city located on the north coast of the island of Java, Indonesia. This city became the forerunner of the Marine Corps is famous for marine affairs and fisheries. Fishing villages, fishing industry, and harbor thrive in this city's. Aside from being a field of industry and business, the potential for ocean Tegal is also used as a recreational area because it has a beautiful view. Bahari Technopark Tegal is a container that is expected to be the forerunner of Tegal Smartcity. Smart in exploiting local potential for Tegal progress both in economic, social, and education. Bahari Technopark Tegal bring together community, government, academia, and industry to work in synergy to create innovative or make an effort in order to improve people's welfare and progress of Tegal independent, sustainable. In addition, Bahari Technopark Tegal is also expected to be a recreational, interesting for anyone to visit and gain insight in particular in the maritime field. Long story short, Bahari Technopark Tegal just like a rowboat, which when rowed by one person then it will be hard to go forward. However, if done together and compact, then made rapid progress is not impossible.